Menghadapi Tantangan Digital: Peran Literasi Digital Dalam Mewujudkan Tujuan Pembangunan Berkelanjutan - Dhea Adinda Syafitri; Sutiawati Sutiawati; Ichsan Fauzi Rachman (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
Digital challenges have become a major focus in the sustainable development agenda, with digital literacy being key to addressing these challenges. This article aims to analyze how digital literacy plays a role in realizing the Sustainable Development Goals (SDGs) in Indonesia. The research utilizes a literature review, which includes a variety of related literature, such as journals, books, and research reports. The results show that digital literacy is essential to support quality education, reduce social and economic disparities, and promote inclusive economic growth. To reap the full benefits of digital literacy, there are still challenges such as the digital divide and unequal access. Therefore, digital literacy is essential to face the challenges and realize the vision of sustainable development in this digital era.